Pengaruh Kebijakan Dividen, Kualitas Laba, Dan Corporate Social Responsibility Terhadap Nilai Perusahaan - Nadira Fairuz Sahara; Anggun Anggraini (CV. ITTC INDONESIA, 2024)
This research aims to determine the influence of dividend policy, earnings quality and corporate social responsibility on firm value. The type of research used is a quantitative approach with associative methods. The sampling technique for this research is purposive sampling. The population of this research is 45 LQ45 companies listed on the Indonesian stock exchange and after following the sampling criteria there are 12 companies with a research period of 5 years producing 60 observation data. The data analysis technique used is panel data regression using the E-views 12 application. Based on the results obtained from the F test, it shows that dividend policy, earnings quality and corporate social responsibility simultaneously influence firm value. The t test results show that corporate social responsibility has a negative effect on company value, while dividend policy and earnings quality have no effect on company value.